Epidemiology of inflammatory bowel disease among participants of the Millennium Cohort: incidence, deployment‐related risk factors, and antecedent episodes of infectious gastroenteritis. Issue 8 (23rd February 2017) - Porter, C. K.; Welsh, M.; Riddle, M. S.; Nieh, C.; Boyko, E. J.; Gackstetter, G.; Hooper, T. I.
Summary: Background: Crohn's disease (CD) and ulcerative colitis (UC) are two pathotypes of inflammatory bowel disease (IBD) with unique pathology, risk factors and significant morbidity. Aim: To estimate incidence and identify IBD risk factors in a US military population, a healthy subset of the US population, using information from the Millennium Cohort Study. Methods: Incident IBD was identified from medical encounters from 2001 to 2009 or by self‐report. Our primary risk factor of interest, infectious gastroenteritis, was identified from medical encounters and self‐reported post‐deployment health assessments. Other potential risk factors were assessed using self‐reported survey responses and military personnel files. Hazard ratios were estimated using Cox proportional hazards analysis. Results: We estimated 23.2 and 21.9 diagnoses per 100 000 person‐years, respectively, for CD and UC. For CD, significant risk factors included [adjusted hazard ratio (aHR), 95% confidence interval]: current smoking (aHR: 2.7, 1.4–5.1), two life stressors (aHR: 2.8, 1.4–5.6) and prior irritable bowel syndrome (aHR: 4.7, 1.5–15.2). There was no significant association with prior infectious gastroenteritis. There was an apparent dose–response relationship between UC risk and an increasing number of life stressors. In addition, antecedent infectious gastroenteritis was associated with almost a three‐fold increase in UC risk (aHR: 2.9, 1.4–6.0). Moderate alcohol consumption (aHR: 0.4, 0.2–0.6) was associated with lower UC risk. Conclusions: Stressful conditions and the high risk of infectious gastroenteritis in deployment operations may play a role in the development of IBD in military populations. However, observed differences in risk factors for UC and CD warrant further investigation. Abstract : Linked Content This article is linked to Porter et al papers. To view these articles visithttps://doi.org/10.1111/apt.14077 andhttps://doi.org/10.1111/apt.14088 .